A Study on Role Conflict in Polytechnic Teachers and Designing Strategies to Minimise Role Conflict - Gupta, B. L.; Jamuar, A. K. (Journal of Engineering Education Transformations, 1997)
The National Policy on Education, 1986 has underlined the need for reorganising the technical and management education system to effectively deal I with the changes in economy, social envieronment, production and management process, rapid expansion of knowledge and advances in science and technology.